Systematic Evaluation of Clinical Efficacy of Shiyiwei Shenqi (Ginseng and Astraglus, Eleven Ingredients) Preparation in Adjuvant Chemotherapy for Malignant Tumor - Bowei HUANG; Yuhui ZENG; Lisha LU; Huijuan GAN (康复学报)
Objective:To evaluate the clinical efficacy and safety of Shiyiwei Shenqi preparation adjuvant chemotherapy in the treatment of malignant tumors by Meta analysis.Methods:Data were search from the databases of CBM, CNKI, Wanfang Data, VIP, PubMed, Web of Science, Cochrane Library and EMbase. Patients with malignant tumors were included in the randomized controlled trials (RCTs) who were treated with Shiyiwei Shenqi preparation in adjuvant chemotherapy. The retrieval time for each database was from the establishment of the database to August 2020. Two researchers independently screened the literature, extracted the data and evaluated the quality of the included studies. RevMan 5.1 software was used to analyze the data. According to the systematic evaluation manual provided by Cochrane Collaboration, the continuity variables used mean difference (MD) and 95%confidence interval (CI) as effect indexes, the dichotomous used odds ratio (OR) and 95%CI as effect indexes. Heterogeneity was determined by χ2test and I2test, When P≥0.1 and I2≤50%, the fixed-effect model would be used, When P< 0.1 or I2> 50%, the random effect model would be used. Outcome indicators were: clinical efficacy (effective rate, stability rate), karnofsky performance scale, bone marrow suppression (white blood cells, hemoglobin), gastrointestinal reactions (nausea, vomiting), liver and renal function, etc.Results:A total of nine RCTs were included, including 633 patients, with 318 cases in the experimental group, 315 cases in the control group. Meta analysis results showed that: compared with the control group, the experimental group can increase the clinical stability rate of patients with malignant tumors[OR=1.73, 95%CI(1.10, 2.73), P=0.02], improve the quality of life[OR=2.77, 95%CI(1.80, 4.28), P< 0.000 01], increase the white blood cell count[OR=0.41, 95%CI(0.27, 0.61), P< 0.000 01], increase the hemoglobin content[OR=0.38, 95%CI(0.23, 0.63), P=0.000 2], reduce gastrointestinal reactions[OR=0.27, 95%CI(0.12, 0.60), P=0.000 2], and reduce the incidence of renal function[OR=0.27, 95%CI(0.12, 0.59), P=0.001]. However, there was no significant difference in reducing the incidence of liver function damage between two groups[OR=0.34, 95%CI(0.12, 1.00), P=0.05], and the difference was not statistically significant.Conclusion:The application of Shiyiwei Shenqi preparation in the treatment of malignant tumor can effectively improve the stability rate of clinical efficacy, improve the bone marrow suppression and renal function, reduce the gastrointestinal reaction of chemotherapy, improve the quality of life of patients, and ensure the treatment is safety. In further studies, more high-quality, large-sample randomized controlled trials are still needed for further verification to provide a more reliable evidence-based basis for clinical practice.